Biochemical Changes as Early Markers of Adverse Neuro-developmental Outcome in Multisystem Inflammatory Syndrome-Neonate - Devika Sanil Kumar; Lal Devayani Vasudevan Nair; Perumalsathya Sankaranarayanan; Harshitha Shanmuganathan; Santosh Kamalakannan (New Advances in Medicine and Medical Science Vol. 5, 2023)
This study was conceived to identify the biochemical markers during neonatal period which correlate with neurodevelopmental outcome, so that even when screening and early imaging gives no clues, clinicians can be on guard about later onset of delays. The multisystem inflammatory syndrome-Newborn (MISC-N) occurs in male babies born to Covid positive mothers and is a sign that the mother has Covid-19, making pregnant women and newborns particularly susceptible to it. Sixteen newborns born to Covid positive mothers were enrolled prospectively in this study after getting informed consent at 40 weeks of gestational age. Newborns with MIS-N with proven antibody titers and newborns with positive Covid testing for the mother at delivery were included in the study. Demographic profile, treatment details and biochemical parameters were analyzed with neurodevelopmental follow-up. 25% mothers received 2 doses of Covid vaccine; 50% had oligohydromnios and 75% received antenatal steroids. 87.5% were preterm of which 62.5% required surfactant with ventilator support and 75% required ionotropic support. Significant association was found between the antibody level and D-dimer levels with the ferritin and LDH levels of the baby (p < 0.05); gestational age with LDH and D-dimer levels (p < 0.05) and Covid antibody level of the baby vs the duration of ventilator requirement (P-value-0.0009). Babies born to Covid positive mothers should be included in the high-risk newborn category and should be strictly monitored and followed up for early identification of neurodevelopmental and neurobehavioral problems and early stimulation and intervention. D-dimer values of babies were positively associated with both maternal antibody and D-dimer levels. Neurodevelopmental follow-up done at 6 months of corrected gestational age showed 37.5% were normal, 37.5% hypertonic and 25% hypotonic. HINE score was below 60 in 62.5%. Development assessment using Bayley-III showed a delay in the motor domain (62.5%), cognitive domain (56.25%) and language domain (62.5%). Hence, it should be born in mind that neurodevelopmental problems occur in babies born to Covid positive mothers and should be stratified as “high risk”. Anticipatory guidance should be given to prospective mothers for preterm care. Covid antibody titre and D-dimer levels may help to predict the NICU stay, ventilator requirement and the adverse neuro-developmental outcomes in these babies.